Compliance Audit Issues of State-owned Business Associations - Boros, Anita (Public Finance Quarterly, 2019)
State-owned business associations have a peculiar role in the system of governmental exercising of (public) functions. They have to comply with the legislative regulations, the objectives set for the business association concerned already upon the formation, the regulations set on owner or - as the case may be - government level, the policy (sector)-level regulations and standards, the expectations of the parties using the public service, the short, medium and long-term strategic objectives the organisation set for itself, the corporate values set for the managers and the employees. Our study is aimed at answering the question whether there are any guidelines for the state-owned business associations, or how the compliance of the state-owned business associations could be audited at all. As a result of our research we found that the Hungarian regulation disposes of the topic of compliance only partially, and there is uniform normative regulation hiatus in respect of the state-owned business associations. Based on the review of the regulation applicable to the state administration entities, to the insurance and credit institution sector we drew up those regulatory topics which we propose for consideration in order to establish the compliance audit foundations of state owned business associations.